Emergency Department Attendance after Telephone Triage: A Population‐Based Data Linkage Study. (29th March 2017) - Gibson, Amy; Randall, Deborah; Tran, Duong T.; Byrne, Mary; Lawler, Anthony; Havard, Alys; Robinson, Maureen; Jorm, Louisa R.
Abstract : Objective: To investigate compliance with telephone helpline advice to attend an emergency department (ED) and the acuity of patients who presented to ED following a call. Data Sources/Collection Methods: In New South Wales (NSW), Australia, 2009–2012, all (1.04 million) calls to a telephone triage service, ED presentations, hospital admissions and death registrations, linked using probabilistic data linkage. Study Design: Population‐based, observational cohort study measuring ED presentations within 24 hours of a call in patients (1) with dispositions to attend ED (compliance) and (2) low‐urgency dispositions (self‐referral), triage categories on ED presentation. Principal Findings: A total of 66.5 percent of patients were compliant with dispositions to attend an ED. A total of 6.2 percent of patients with low‐urgency dispositions self‐referred to the ED within 24 hours. After age adjustment, healthdirect compliant patients were significantly less likely (7.8 percent) to receive the least urgent ED triage category compared to the general NSW ED population (16.9 percent). Conclusions: This large population‐based data linkage study provides precise estimates of ED attendance following calls to a telephone triage service and details the predictors of ED attendance. Patients who attend an ED compliant with a healthdirect helpline disposition are significantly less likely than the general ED population to receive the lowest urgency triage category on arrival.